Physical Fitness Profile Analysis: Survey Study On Extracurricular Football Students - Rubiyatno; Putra Sastaman B; Didi Suryadi (Indonesian Journal of Physical Education and Sport Science)
Studi purpose. Physical fitness is one of the important indicators of success in a soccer game. However, during its implementation, students' physical fitness is not paid enough attention and is not even used as a benchmark for preparing training programs. This study aims to determine physical fitness in extracurricular soccer students.